2021
DOI: 10.1186/s12887-021-02601-7
|View full text |Cite
|
Sign up to set email alerts
|

Single-dose azithromycin for child growth in Burkina Faso: a randomized controlled trial

Abstract: Background In lower resource settings, previous randomized controlled trials have demonstrated evidence of increased weight gain following antibiotic administration in children with acute illness. We conducted an individually randomized trial to assess whether single dose azithromycin treatment causes weight gain in a general population sample of children in Burkina Faso. Methods Children aged 8 days to 59 months were enrolled in November 2019 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…A randomized trial 18 in Malawi found that antibiotics improved childhood growth and decreased mortality when given in the setting of severe acute malnutrition, although other similar trials 19 , 20 have found no benefit. A randomized trial 21 from Burkina Faso found greater weight gain among children administered a single dose of azithromycin at 14 days but not at 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…A randomized trial 18 in Malawi found that antibiotics improved childhood growth and decreased mortality when given in the setting of severe acute malnutrition, although other similar trials 19 , 20 have found no benefit. A randomized trial 21 from Burkina Faso found greater weight gain among children administered a single dose of azithromycin at 14 days but not at 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…Physiological criteria, including body and thymus weight, were determined following the methods described by Farhangi et al ( 2017 ) and Kong et al ( 2018 ). The weight gain velocity (Sié et al, 2021 ; Stahr et al, 2021 ) was calculated with the formula below: when: N > 2, M = N ‐2; N = 1, M = 0, …”
Section: Methodsmentioning
confidence: 99%
“…Physiological criteria, including body and thymus weight, were determined following the methods described by Farhangi et al (2017) and Kong et al (2018). The weight gain velocity (Sié et al, 2021; Stahr et al, 2021) was calculated with the formula below: when: N > 2, M = N ‐2; N = 1, M = 0,weight0.5emgain0.5emvelocitygoodbreak=weight0.5emat0.5emN0.5emweeksweight0.5emat0.5emM0.5emweeksweight0.5emat0.5emM0.5emweeksgoodbreak×100%.…”
Section: Methodsmentioning
confidence: 99%
“…Specific antibiotics within these classes, such as azithromycin and Ceftiofur Crystalline Free Acid (CCFA), can be given as a single dose or abbreviated course and offers refinement options for veterinarians as one‐time dosing or abbreviated courses may be utilized. Reports in the literature have shown that a single, high‐dose azithromycin for the treatment of shigellosis in children resulted in increased weight and survivability 11 . In human medicine, a 5‐day tapering dose of azithromycin, also known by brand names Zithromax™ and Z‐Pak™, can be used for a variety of clinical diseases due to its wide spectrum of activity 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Reports in the literature have shown that a single, high‐dose azithromycin for the treatment of shigellosis in children resulted in increased weight and survivability. 11 In human medicine, a 5‐day tapering dose of azithromycin, also known by brand names Zithromax™ and Z‐Pak™, can be used for a variety of clinical diseases due to its wide spectrum of activity. 12 Additionally, CCFA, a fourth generation cephalosporin, has been demonstrated to reach therapeutic concentrations in macaques for at least 7 days when given as a one‐time convenient dose.…”
Section: Introductionmentioning
confidence: 99%